Topographic Organization of Hippocampal Inputs to the Anterior Olfactory Nucleus - Aqrabawi, Afif J.; Kim, Jun Chul (Frontiers in Neuroanatomy, 2018)
Top-down processes conveying contextual information play a major role in shaping odour representations within the olfactory system, yet the underlying mechanisms are poorly understood. The hippocampus (HPC) is a major source of olfactory top-down modulation, providing direct excitatory inputs to the anterior olfactory nucleus (AON). However, HPC-AON projections remain uncharacterized. In an effort to understand how hippocampal inputs are distributed within the AON, we systematically outlined their organization using anterograde and retrograde tracing methods. We found that AON-projecting hippocampal pyramidal neurons are located mostly in the ventral two-thirds of the HPC and are organized topographically such that cells with a ventral to intermediate hippocampal point of origin terminate, respectively, at the medial to lateral AON. Our neuroanatomical findings suggest a potential role for the hippocampus in the early processing and contextualization of odours which merits further investigation.